A tannic acid modified tin disulfide composite film and its preparation method and application

CN118767701BActive Publication Date: 2025-03-18TONGJI UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411236914.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-05
Publication Date
2025-03-18
Estimated Expiration
2044-09-05

AI Technical Summary

Technical Problem

Traditional polymer films have limited selectivity when separating complex dye salt mixtures, resulting in poor dye/salt separation effect, irreversible membrane contamination, and degradation over time reduces membrane performance and increases energy input for wastewater treatment.

Method used

A tin disulfide composite film modified by tannin acid is used. This film uses a tin disulfide composite film to load tannin acid modified tin disulfide nanosheets on the polymer base film, and uses the domain-limiting effect of the interlayer channels between nanosheets to achieve efficient separation of organic pollutants in water.

Benefits of technology

It realizes efficient separation of organic dye molecules in water, maintains high throughput, and has high molecular/ion selectivity, has good permeability to inorganic salt ions, and enhances the stability and anti-pollution ability of the membrane.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118767701B_ABST
    Figure CN118767701B_ABST
Patent Text Reader

Abstract

The present invention relates to a tannic acid modified tin disulfide composite membrane and a preparation method and application thereof. The tannic acid modified tin disulfide composite membrane is loaded with tannic acid modified tin disulfide nanosheets on one surface of a polymer base membrane, the carboxyl group of the tannic acid coordinates with the tin atoms on the tin disulfide nanosheets to achieve modification, and the tin disulfide nanosheets are prepared by lithium ion intercalation. The present invention has the advantages of efficiently separating organic pollutants in water by utilizing the confinement effect of interlayer channels between nanosheets, high ion permeability, antibacterial and anti-pollution properties, etc.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of two-dimensional separation membrane materials, and in particular to a tannic acid-modified tin disulfide composite membrane and a preparation method and application thereof. Background Art

[0002] Water scarcity is a pressing global challenge that requires advanced technologies to achieve sustainable water resources. Membrane separation processes such as reverse osmosis, nanofiltration, and ultrafiltration play a vital role in effectively addressing water treatment needs. These processes are suitable for applications such as desalination and wastewater treatment, providing scalable and reliable methods for pollutant removal. However, dye / salt separation remains a major challenge in the treatment of dye wastewater. Conventional polymer membranes have limited selectivity in separating complex dye-salt mixtures, resulting in poor dye / salt separation and irreversible membrane fouling due to the complex molecular structures of different dye molecules. Over time, this degradation reduces membrane performance, while lower flux increases the energy input for wastewater treatment. As membrane technology advances, addressing these issues is critical to providing effective and sustainable solutions for treating dye-containing wastewater, especially in the context of global water scarcity.

[0003] Two-dimensional layered membranes represented by graphene oxide and transition metal dichalcogenides have shown significant advantages in various applications, especially in membrane separation processes. Their atomic-scale thickness provides higher selectivity, allowing precise control of pore size and effective separation of molecules based on size and charge, making them highly attractive in applications such as water treatment. However, graphene oxide is prone to severe swelling in practical applications due to its surface oxygen-rich groups, resulting in reduced selectivity. Thiometallic disulfide (TMDs) nanosheets have excellent rigidity and smooth non-functionalized surfaces, providing fast transport channels for the transport of water molecules. In addition, studies have shown that the interlayer spacing of dry laminar membranes is narrow, which hinders the penetration of water molecules. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a tannic acid modified tin disulfide composite membrane and its preparation method and application. The present invention has the advantages of efficient separation of organic pollutants in water by utilizing the confinement effect of interlayer channels between nanosheets, high ion permeability and antibacterial and anti-pollution properties.

[0005] The first object of the present invention is to provide a tannic acid-modified tin disulfide composite membrane, wherein the tannic acid-modified tin disulfide composite membrane is loaded with tannic acid-modified tin disulfide nanosheets on one surface of a polymer base membrane, the carboxyl group of the tannic acid coordinates with the tin atoms on the tin disulfide nanosheets to achieve modification, and the tin disulfide nanosheets are prepared by using organic lithium compounds to intercalate lithium ions between tin disulfide layers in an inert gas environment, and realizing the exfoliation of thin layers of tin disulfide under the assistance of ultrasound.

[0006] In some embodiments of the present invention, the polymer base membrane is one of a PVDF membrane, a PES membrane, and a PTFE membrane.

[0007] In some embodiments of the present invention, the loading amount of tannic acid modified tin disulfide nanosheets on the surface of tannic acid modified tin disulfide composite membrane is 0.095-0.286 mg / cm 2 .

[0008] In some embodiments of the present invention, the mass ratio of tin disulfide to tannic acid in the tannic acid-modified tin disulfide nanosheets is 1-2:1.

[0009] The second object of the present invention is to provide a method for preparing the tannic acid-modified tin disulfide composite film, comprising the following steps:

[0010] S1. In an inert atmosphere, tin disulfide powder and an organic lithium compound solution are mixed, and ultrasonic stripping is performed to separate the solid and liquid to obtain a mixed powder;

[0011] S2, ultrasonically dispersing the obtained mixed powder in a tannic acid solution, separating the solid from the liquid to obtain a solid phase, ultrasonically dispersing the obtained solid phase in water, centrifuging to obtain a supernatant, and freeze-drying the obtained supernatant to obtain a tannic acid-modified tin disulfide nanomaterial;

[0012] S3, ultrasonically dispersing the tannic acid-modified tin disulfide nanomaterial, and filtering it on the surface of the polymer base membrane, so as to obtain the tannic acid-modified tin disulfide composite membrane.

[0013] In some embodiments of the present invention, in step S1, the molar ratio of the tin disulfide powder to the organic lithium compound is 1:2-1:4.

[0014] In some embodiments of the present invention, in step S1, the solvent of the organic lithium compound solution is n-hexane; the mass concentration of the organic lithium compound solution is 8%-16%; and the organic lithium compound in the organic lithium compound solution is selected from n-butyl lithium.

[0015] In some embodiments of the present invention, in step S1, the mixing time is 24-48 h; the ultrasonic power of ultrasonic peeling is 80-180 W, and the time is 1-2 h;

[0016] The solid-liquid separation method adopts high-speed centrifugation, and the rotation speed of the high-speed centrifugation is 4000 r / min~12000 r / min.

[0017] In some embodiments of the present invention, the concentration of the tannic acid solution is 1-3 mg / mL.

[0018] The third object of the present invention is to provide the use of the tannic acid modified tin disulfide composite membrane in separating organic dye molecules in water.

[0019] In the present invention, the tannic acid-modified tin disulfide nanosheets utilize organic lithium compounds to intercalate lithium ions into tin disulfide interlayers under an inert gas environment, and thin layers of tin disulfide are prepared by exfoliation under the assistance of ultrasound. Afterwards, the carboxyl groups in the tannic acid and the tin atoms in the tin disulfide nanosheets are coordinated so that the tannic acid molecules can be adsorbed on the surface of the nanosheets. The presence of the surface tannic acid enhances the dispersibility and stability of the hydrophobic tin disulfide nanosheets in water on the one hand, and on the other hand, as an intercalation molecule, expands the interlayer distance of the tin disulfide nanosheets, so that the space size is sufficient for water molecules to pass through.

[0020] The above technical solution of the present invention has the following advantages compared with the prior art:

[0021] (1) Compared with other sulfide metal compounds, the raw material elements of the tin disulfide nanosheets of the present invention have higher content in nature, more abundant reserves, and low price.

[0022] (2) The tannic acid-modified tin disulfide nanosheets of the present invention have better dispersion stability in water than unmodified two-dimensional materials, and the hydrophilicity of the nanosheets is improved by tannic acid modification.

[0023] (3) The nanosheets in the composite membrane obtained by the present invention construct nanoscale interlayer channels, which not only ensure high flux but also have high molecular / ion selectivity, have a high efficiency in removing dye molecules in water, and have good permeability to inorganic salt ions. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to make the content of the present invention more clearly understood, the present invention is further described in detail below according to specific embodiments of the present invention in conjunction with the accompanying drawings, wherein:

[0025] Figure 1The stability comparison is between the tannic acid modified tin disulfide nanosheet dispersion prepared in Example 1 of the present invention and the unmodified single tin disulfide nanosheet dispersion prepared in Comparative Example 1;

[0026] Figure 2 This is an image of the tannic acid-modified tin disulfide composite film prepared in Example 1 of the present invention;

[0027] Figure 3 This is the surface SEM test result of the tannic acid modified tin disulfide composite film prepared in Example 1 of the present invention;

[0028] Figure 4 FTIR test results of the tannic acid modified tin disulfide composite film prepared in Example 1 of the present invention;

[0029] Figure 5 The dye separation performance of different composite membranes in Example 1 and Comparative Example 2 of the present invention. DETAILED DESCRIPTION

[0030] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention. Example 1

[0031] This embodiment provides a preparation method and application of a tannic acid modified tin disulfide composite film.

[0032] (I) Preparation method of tannic acid modified tin disulfide composite film

[0033] (1) Disperse 600 mg of commercial tin disulfide powder in 8 mL of 0.8 mol / L n-butyl lithium solution, stir thoroughly for 48 h, wash three times with n-hexane, and filter to obtain lithium-intercalated tin disulfide black powder.

[0034] (2) The product obtained in step (1) was quickly transferred into an aqueous solution for ultrasonic-assisted exfoliation at an ultrasonic power of 180 W for 1 h.

[0035] (3) The brown solution obtained by ultrasonic stripping in step (2) was transferred to a centrifuge tube and centrifuged at 12000 r / min for 30 min, three times in total, to wash away the residual lithium ions and n-hexane, and collect the precipitate at the bottom.

[0036] (4) The brown precipitate obtained in step (3) was transferred to a jacketed beaker and ultrasonically dispersed in 100 ml of 3 mg / L tannic acid solution at 180 W for 30 min.

[0037] (5) The brown solution obtained by ultrasonic stripping in step (4) was transferred to a centrifuge tube and centrifuged at 12000 r / min for 30 min, three times in total, to wash away excess tannic acid and collect the precipitate at the bottom.

[0038] (6) The brown precipitate obtained in step (5) was transferred to a jacketed beaker and ultrasonically dispersed in ultrapure water at a power of 180 W for 30 min. The dispersion was then centrifuged at 4000 r / min and the supernatant was collected.

[0039] (7) The supernatant solution obtained in step (6) is placed in a freeze dryer and freeze-dried for 48 hours to obtain the final tannic acid-modified tin disulfide nanosheet material.

[0040] (8) The powder obtained in step (7) was ultrasonically dispersed to 0.1 mg / L, 12 ml of the dispersion was taken, and vacuum filtered to the surface of a 4 cm diameter PVDF membrane. After the filtration was completed, it was stored in water to obtain a tannic acid modified tin disulfide composite membrane.

[0041] Comparative Example 1

[0042] Similar to the embodiment, the difference is that in step (4), tannic acid is not added, and a single tin disulfide nanosheet is obtained.

[0043] Comparative Example 2

[0044] Comparative Example 2 uses a blank PVDF membrane without tannic acid-modified tin disulfide nanosheets to perform a dye filtration separation test.

[0045] The stability comparison of the tannic acid modified tin disulfide nanosheet dispersion obtained in step (8) of this embodiment and the single tin disulfide nanosheet dispersion obtained in comparative example 1 without adding tannic acid is shown in the figure below. Figure 1 As shown in FIG. 1 , after a single tin disulfide nanosheet dispersion was placed for 6 weeks, the nanosheets began to aggregate and settle. The TEM image of the tannic acid-modified tin disulfide nanosheet material obtained in step (7) is shown in FIG. Figure 2 As shown, the FTIR characterization results of the tannic acid-modified tin disulfide composite film obtained in step (7) are as follows Figure 3 As shown in Figure 2, it shows that tannic acid is successfully modified on the surface of tin disulfide nanosheets. The SEM image of the prepared tannic acid modified tin disulfide composite film is as follows: Figure 4 shown.

[0046] (II) Dye separation experiment under cross-flow filtration conditions

[0047] Under 1 bar pressure, 30 mg / L Congo red solution was used as feed solution to evaluate the performance of the composite membrane in separating dye molecules in water. The reaction device consists of a pump, a membrane tank, and a balance.

[0048] The obtained tannic acid modified tin disulfide composite membrane was pre-pressed with ultrapure water for 15 min. After the flux of ultrapure water filtered by the tannic acid modified tin disulfide composite membrane stabilized, the influent water was changed to Congo red solution. After filtering for 30 min, the flux was calculated using an analytical balance, and the absorbance was measured using an ultraviolet spectrophotometer to calculate the Congo red concentration in the water. The permeability and Congo red retention rate of the composite membrane are shown in Figure 2. Figure 5 As shown by Figure 5 It can be seen that the loading amount reaches 0.18 mg / cm 2 Afterwards, the retention rate of Congo red dye by the composite membrane was higher than 98%. Example 2

[0049] (i) The preparation method is the same as that of Example 1, except that in step (8): 12 ml of the dispersion liquid is adjusted to 17 ml.

[0050] (II) Dye separation experiment under cross-flow filtration conditions

[0051] The evaluation method of the composite membrane dye separation performance in this example is the same as that in Example 1. The permeability and Congo red rejection of the composite membrane are shown in Figure 4 shown. Example 3

[0052] (i) The preparation method is the same as that of Example 1, except that in step (8): 12 ml of the dispersion liquid is adjusted to 24 ml.

[0053] (II) Dye separation experiment under cross-flow filtration conditions

[0054] The method for evaluating the dye separation performance of the tannic acid modified tin disulfide composite membrane obtained in this example is the same as that in Example 1. Example 4

[0055] (i) The preparation method is the same as that of Example 1, except that in step (8): 12 ml of the dispersion liquid is adjusted to 37 ml.

[0056] (II) Dye separation experiment under cross-flow filtration conditions

[0057] The dye separation performance evaluation method of the obtained tannic acid modified tin disulfide composite membrane in this example is the same as that in Example 1. The permeability and Congo red rejection rate of the obtained tannic acid modified tin disulfide composite membrane are shown in Figure 4 shown.

[0058] from Figure 4 It can be seen that in Examples 1-3, as the loading amount of the nanomaterial increases, the interception rate of the composite membrane for Congo red gradually increases, and Example 3 has a high flux while ensuring a high interception rate.

[0059] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.

Claims

1. A tannic acid modified tin disulfide composite film, characterized in that: The tannic acid-modified tin disulfide composite membrane is loaded with tannic acid-modified tin disulfide nanosheets on one surface of a polymer base membrane, the carboxyl group of the tannic acid coordinates with the tin atoms on the tin disulfide nanosheets to achieve modification, and the tin disulfide nanosheets are prepared by lithium ion intercalation; the tannic acid-modified tin disulfide composite membrane is prepared by the following method: S1. In an inert atmosphere, tin disulfide powder and an organic lithium compound solution are mixed, and ultrasonic stripping is performed to separate the solid and liquid and obtain a solid phase to obtain a mixed powder; the organic lithium compound of the organic lithium compound solution is n-butyl lithium; S2, ultrasonically dispersing the obtained mixed powder in a tannic acid solution, separating the solid from the liquid to obtain a solid phase, ultrasonically dispersing the obtained solid phase in water, centrifuging to obtain a supernatant, and freeze-drying the obtained supernatant to obtain a tannic acid-modified tin disulfide nanomaterial; S3, ultrasonically dispersing the tannic acid-modified tin disulfide nanomaterial, and filtering it on the surface of the polymer base membrane, so as to obtain the tannic acid-modified tin disulfide composite membrane.

2. The tannic acid-modified tin disulfide composite film according to claim 1, characterized in that: The polymer base membrane is one of a PVDF membrane, a PES membrane and a PTFE membrane.

3. The tannic acid-modified tin disulfide composite film according to claim 1, characterized in that: The loading amount of tannic acid modified SnS2 nanosheets on the tannic acid modified SnS2 composite membrane is 0.095-0.286 mg / cm 2 .

4. The tannic acid-modified tin disulfide composite film according to claim 1, characterized in that: The mass ratio of tin disulfide to tannic acid in the tannic acid-modified tin disulfide nanosheets is 1-2:

1.

5. The tannic acid-modified tin disulfide composite film according to claim 1, characterized in that: In step S1, the molar ratio of the tin disulfide powder to the organic lithium compound is 1:2-1:

4.

6. The tannic acid-modified tin disulfide composite film according to claim 1, characterized in that: In step S1, the solvent of the organic lithium compound solution is n-hexane; The mass concentration of the organic lithium compound solution is 8% to 16%.

7. The tannic acid-modified tin disulfide composite film according to claim 1, characterized in that: In step S1, the mixing time is 24-48 h; the ultrasonic power of ultrasonic stripping is 80-180 W, and the time is 1-2 h; The solid-liquid separation method adopts high-speed centrifugation, and the rotation speed of the high-speed centrifugation is 4000 r / min~12000 r / min.

8. The tannic acid-modified tin disulfide composite film according to claim 1, characterized in that: The concentration of the tannic acid solution is 1-3 mg / mL.

9. Use of the tannic acid-modified tin disulfide composite membrane according to any one of claims 1 to 8 in separating organic dye molecules in water.

Citation Information

Patent Citations

  • Tin disulfide intercalation compound and hydrothermal synthesis method thereof

    CN102838161A

  • Method for preparing large-size ultrathin molybdenum disulfide nanosheet through chemical intercalation assisted liquid phase stripping and product prepared through method

    CN113104892A